The more important particularities of teenager's spiritual growth in modern school - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 1998)
Cognition, love and creation express spiritual growth most of all. The senior teenagers appreciate most favourable love. Its displays appear in standpoint, emotional and behavioural levels. The science is more important in one’s behaviour evaluation. The importance of creation everywhere is the lowest.
Keywords: students; spirituality; spiritual values; teenager's spiritual growth